The Pemekaran Wilayah di Indonesia Pasca Reformasi dalam Rangka Penyelenggaraan Otonomi Daerah: Indonesia - Marfuah; Nofrizal (UIR Press, 2025)
Abstract: This study examines the phenomenon of regional expansion in Indonesia in the post-reformation era within the context of implementing regional autonomy. Regional expansion has become a crucial issue following the adoption of decentralization policies that grant greater authority to local governments. This research uses a normative legal method with statutory, historical, and conceptual approaches. The study focuses on analyzing the legal instruments governing regional expansion and the factors driving such processes. Based on the analysis, regional expansion is regulated under Article 18 of the 1945 Constitution and further reinforced by Law No. 23 of 2014 on Regional Government and Government Regulation No. 78 of 2007. The main driving factors include administrative effectiveness, desires for social homogeneity, fiscal incentives, and local elite interests. The study concludes that although regional expansion aims to improve public services and local welfare, its implementation still faces numerous challenges, including inadequate regional preparedness and the dominance of political interests. A comprehensive evaluation of expansion policies is necessary to ensure alignment with the primary goals of regional autonomy. Keywords: Regional Expansion, Regional Autonomy, Decentralization, Local Government, Post-Reformation.